Eggs as a Suitable Tool for Species Diagnosis of Causative Agents of Human Diphyllobothriosis (Cestoda) - Leštinová, Kateřina (Jihočeská univerzita, 2016)
More than 2,000 eggs of 8 species of diphyllobothriid cestodes infecting humans were compared. Combination of morphometrical and ultrastructural (surface morphology) data made it possible to distinguish all species.
Eggs as a Suitable Tool for Species Diagnosis of Causative Agents of Human Diphyllobothriosis (Cestoda)
Keywords: Cestoda; Tapeworms; Diphyllobothrium; eggs; SEM; Human Diphyllobothriosis; ultrastrucure; morphometry; Cestoda; Tapeworms; Diphyllobothrium; eggs; SEM; Human Diphyllobothriosis; ultrastrucure; morphometry